3PC-009 Successful treatment of hamartoma in child syndrome after 30 months with topical administration of simvastatin/cholesterol cream: a case report. (March 2019) - Crametz, H; Lannoy, D; Catteau, B; Foulon, V; Nassar, C; Roche, M; Odou, P
Abstract : Background: Congenital hemidysplasia with ichthyosiform erythroderma and limb defects syndrome (CHILD) syndrome is a rare X-linked dominant disorder of cholesterol metabolism that clinically expresses as an epidermical hamartoma. Using co-application of topical formulation of simvastatin and cholesterol (TFSC) on skin lesions after previous failures has recently been reported. 1 Purpose: To describe protocol of use, efficacy and safety of TFSC. Material and methods: A woman, born in 1988, presented at birth with an extensive epidermal hamartoma due to CHILD syndrome. The cutaneous presentation was ichtyosiform erythroderma with sharp midline demarcation involving the right side of the body and a homolateral lower limb. She had skeletal malformations of her upper and lower limbs. Partial lower limb amputation was necessary when she was 2 years' old. In February 2016, since skin lesions did not improve with acitretine, topical corticoid and various types of dressings, TFSC was began after obtaining informed consent. We developed an original ethanol-free formulation with simvastatin, cholesterol in Excipial Lipocreme (Galderma). The preparation consists of incorporating simvastatin in powder and triturated ground powder of cholesterol with Excipial: physical stability was satisfactory for at least 30 days. We used the following protocol 1 : in the first month, 0.5% simvastatin and cholesterol in Excipial Lipocreme, twice per day on a limited area to test tolerance; then afterwards at 2%, twice per day on a wider area. Efficacy was clinically assessed (aspect and extension of the skin lesion) and tolerance was clinically and biologically assessed. Results: TFSC was started in February 2016. Erythema whitened after 10 months and totally disappeared after 18 months. After 24 months, improvement began on the papillomatous aspect of the stump. After 30 months, whitening areas were stable, with persisting papillomatosis in the stump and flexion areas. A 2 month supply disruption of simvastatin powder during the first year led to the reappearance of erythema. When TFSC resumed, the lesions improved again. The main reported side effect was the skin's dryness on application, leading to emollient use. Complete blood counts, electrolytes, urea, triglycerides, cholesterol, CPK and liver function remained normal. Conclusion: This case shows the interest and safety of TFSC in hamartoma lesions, indicating a potential interest in other types of hamartoma. Reference and/or acknowledgements: Alexopoulos A, Kakourou T. Pediatr Dermatol 2015;32:e145–7. No conflict of interest.